ARNT/HIF‐1β links high‐risk 1q21 gain and microenvironmental hypoxia to drug resistance and poor prognosis in multiple myeloma. (21st June 2018) - Wu, Chuan; Yang, Ting; Liu, Yingmin; Lu, Yicheng; Yang, Yanping; Liu, Xiaobo; Liu, Xuelian; Ye, Long; Sun, Yue; Wang, Xue; Li, Qingchao; Yang, Peiyu; et al.
Abstract: 1q21 gain is a common cytogenetic abnormality featuring high‐risk multiple myeloma (HRMM). However, the molecular mechanism underlying the adverse prognostic effect of 1q21 gain remains largely unclear. Here, we report that ARNT /HIF‐1β, a 1q21 gene, is highly expressed in HRMM and induced by microenvironmental hypoxia, which confers drug resistance and correlates with inferior outcome. Analysis of the gene expression profile database revealed that ARNT expression was upregulated in MM and increased with disease progression or in HRMM subtypes (particularly 1q21 gain), while correlated to shorter overall survival. In a cohort of 40 MM patients, qPCR further validated that ARNT expression was higher in MM patients than normal donors. MM cells carrying 1q21 gain or acquired drug resistance displayed a robust increase in HIF‐1β protein level. Hypoxia induced HIF‐1β expression via a NF‐κB‐dependent process. Notably, HIF‐1β overexpression impaired bortezomib sensitivity, whereas shRNA knockdown of ARNT reversed hypoxia‐mediated drug resistance. Together, these findings suggest that ARNT /HIF‐1β might represent a novel biomarker for risk stratification and prognosis of HRMM patients, as well as a potential therapeutic target for overcoming 1q21 gain‐ or microenvironment‐mediated and acquired drug resistance in MM. Abstract : (1) ARNT/HIF‐1β is highly expressed in multiple myeloma (MM) and correlates with poor prognosis; (2) ARNT/HIF‐1β expression is associated with high‐risk MM carrying 1q21 gain; (3) ARNT/HIF‐1β overexpression contributes to both hypoxia‐ mediated and acquired drug resistance.